Improving the criteria for quality assessment of image processing algorithms; Journal of Physics: Conference Series; Vol. 1862 : Electronic Devices and Control Systems (EDCS 2020) - Kochegurov A. I. Aleksandr Ivanovich (2021, 2021)
Title screen